Geochemical Modeling of Water-Rock Interaction Processes in the Pollino National Park - C. Apollaro; I. Fuoco; L. Bloise; E. Calabrese; L. Marini; G. Vespasiano; F. Muto (Geofluids)
This work is aimed at reconstructing the water-rock interaction processes controlling the geochemical characteristics of the shallow or relatively shallow groundwaters of the Pollino National Park, based on the data acquired for 105 water samples from local springs. Reaction path modeling of rock dissolution was carried out in a purely stoichiometric mode for the main lithotypes cropping out in the study area, that is, limestone, Mg-limestone, dolomite, serpentinite, Al-silicate fraction of calcschist, and carbonate fraction of calcschist. Reaction path modeling was carried out in a purely stoichiometric mode, considering the rocks of interest as materials of known stoichiometry and unknown thermodynamic properties. Calculations were carried out assuming a closed system for secondary solid phases whereas an open system was assumed for gases, O2(g) and CO2(g). Comparison of the results of geochemical modeling and the analytical data acquired for the groundwaters of the Pollino National Park shows that concentrations of major solutes, SiO2, Li, Al, and Fe of the different chemical types of waters, are explained by the dissolution of pertinent lithotypes. Moreover, the detected concentrations of Al, Cl, F, NO3, and SO4 are within the threshold values recommended by WHO.